THE DEVELOPMENT OF DOMESTIC TOURISM AND ITS INFLUENCE IN THE REPUBLIC UZBEKISTAN (Academicia Globe: Inderscience Research, 2024)
The article highlights the key developments in Uzbekistan's tourism industry. The industry's development of tourism is a significant sector that is intimately tied to the nation's overall development. One of the primary indications of today's state of affairs is the organization of tourist-related services and the development of tourism concepts.